All‐Liquid Reconfigurable Electronics Using Jammed MXene Interfaces. Issue 13 (22nd February 2023) - Popple, Derek; Shekhirev, Mikhail; Dai, Chunhui; Kim, Paul; Wang, Katherine Xiaoxin; Ashby, Paul; Helms, Brett A.; Gogotsi, Yury; Russell, Thomas P.; Zettl, Alex
Abstract: Rigid, solid‐state components represent the current paradigm for electronic systems, but they lack post‐production reconfigurability and pose ever‐increasing challenges to efficient end‐of‐life recycling. Liquid electronics may overcome these limitations by offering flexible in‐the‐field redesign and separation at end‐of‐life via simple liquid phase chemistries. Up to now, preliminary work on liquid electronics has focused on liquid metal components, but these devices still require an encapsulating polymer and typically use alloys of rare elements like indium. Here, using the self‐assembly of jammed 2D titanium carbide (Ti3 C2 T x ) MXene nanoparticles at liquid–liquid interfaces, "all‐liquid" electrically conductive sheets, wires, and simple functional devices are described including electromechanical switches and photodetectors. These assemblies combine the high conductivity of MXene nanosheets with the controllable form and reconfigurability of structured liquids. Such configurations can have applications not only in electronics, but also in catalysis and microfluidics, especially in systems where the product and substrate have affinity for solvents of differing polarity. Abstract : Structured liquids provide a route to self‐assemble functional materials at the liquid–liquid interface and to shape liquids into arbitrary geometries. In this work, the high conductivity of MXenes is leveraged to create conductive pathways at the interface. The electrical properties of the assemblies are characterized and initial all‐liquid electronic devices are presented.